Pengaruh Pengawasan Preventif dan Pengawasan Detektif terhadap Efektifitas Pengendalian Anggaran - Arif Fajri (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
This study aims to examine the extent of the influence of preventive controlsconducted prior to budget execution and detective supervision after the implementation ofthe budget on the effectiveness of the control of the budget. By knowing how much theinfluence of detective and preventive supervision control on the effectiveness of budgetcontrol is expected to be a study to further improve the effectiveness of this oversight ofbudgetary control. Ineffective supervision will open loopholes for budgetary aberrations,so the procedures that have been made are ineffective in ensuring the implementation ofbudgetary control. The object of this research is echelon II, echelon III, and echelon IVofficials in Padang city government. This study belongs to causative research which seesthe extent of causality between two or more variables. To obtain data and materials neededin this research used field research with sampling technique from this research is purposivesampling, that is sampling from population based on certain criterion or based on researchpurpose.